Using Big Data Methods in Bandung City Planning Research: Urban Resilient Governance with Smart City - Abdillah Abdillah; Ida Widianingsih; Rd Ahmad Buchari; Heru Nurasa (Dealings Foundation Institute, 2025)
This study explores the significance of big data methods in urban planning, focusing on their application in Bandung City’s smart city initiatives, the challenges involved, and their potential in foster a resilient urban environment. This research adopts a descriptive approach, utilizing big data methods to analyze urban resilience governance within the smart city framework of Bandung City. The study provides insights into the challenges, ethical considerations, and potential benefits of applying big data methods in urban planning for Bandung City. It also examines the concept of resilient urban governance in the development of smart cities. However, this study does not specifically analyze a particular case in Bandung City. Instead, it aims to offer valuable perspectives on the role of big data in broader urban planning and key strategies that can be applied to enhance urban governance resilience—both in Bandung City and in other cities facing similar challenges and opportunities. Integrating big data methods into Bandung City's urban planning is a crucial step toward achieving resilient governance in the context of a smart city. By leveraging advanced data analytics, cities can enhance decision-making processes, optimize resource management, and improve public services, ultimately fostering a more sustainable and liveable urban environment.